Evaluating the Performance of Stool Antigen Tests to Detect Helicobacter pylori Infection in Tobruk, Libya - Eisa Omar (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Infection by Helicobacter pylori (H. pylori) occurs in half of the general population worldwide, with high geographic variability. Even though H. pylori is the leading cause of several gastric diseases, ranging from gastritis and peptic ulcers to gastric malignancies such as gastric cancer and mucosa-associated lymphoid tissue lymphoma, most of the infections remain asymptomatic. Early detection and eradication of H. pylori can definitely prevent severe long-term gastric diseases associated with the bacteria. In Libya, the prevalence of H. pylori is not well documented, especially in healthy subjects. The aim of this study is to evaluate the performance of a stool antigen test for H. pylori in people from Tobruk, Libya. Methods. The present study was conducted on 130 stool samples, including both children and adults. The present study was carried out at the polyclinic in Tobruk, Libya. Results. A total of 130 symptomatic patients selected randomly (50 males and 80 females; age range of 5 to 80 years) were studied. Out of the 130 participants screened, 70 (53.84%) were positive, while 60 (46.15%) were negative for H. pylori stool antigen. To detect H. pylori antigen in feces, the TECAN fecal antigen and the ELISA enzyme-linked immunoassay for the quantitative and qualitative determination of Helicobacter pylori antigen in feces were used. Conclusion. In this study, the stool antigen test, a low-cost and rapid diagnostic technique, proved to be highly sensitive and specific for detecting H. pylori infection.